PENGARUH ENTREPRENEURIAL ORIENTASI DAN KEMAMPUAN MANAJERIAL TERHADAP KINERJA PEGAWAI DI MEDIASI OLEH KEPUASAN KERJA PADA PEGAWAI YAYASAN IKLAS MULYA HATI INSANI DI KECAMATAN WARUNGGUNUNG - Novi Kurniawati; M. Mudzakkir; Eris (The Asia Pacific Journal Of Management Studies, 2026)
This study aims to analyze the effect of entrepreneurial orientation and managerial capability on employee performance, mediated by job satisfaction among employees of Yayasan Iklas Mulya Hati Insani in Warunggungung District. The research method used is a quantitative approach with data collection techniques through questionnaires. The population in this study includes all foundation employees, with a saturated sampling method applied. Data analysis was conducted using path analysis to examine both direct and indirect relationships among variables. The results show that entrepreneurial orientation and managerial capability have a positive and significant effect on job satisfaction. Furthermore, entrepreneurial orientation and managerial capability also have a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance and is proven to mediate the relationship between entrepreneurial orientation, managerial capability, and employee performance. Therefore, improving entrepreneurial orientation and managerial capability supported by job satisfaction can optimally enhance employee performance.